Oligothienylenevinylene Polarons and Bipolarons Confined between Electron‐Accepting Perchlorotriphenylmethyl Radicals. Issue 15 (14th February 2018) - Mayorga Burrezo, Paula; Franco, Carlos; Caballero, Rubén; Mas‐Torrent, Marta; Langa, Fernando; López Navarrete, Juan T.; Rovira, Concepció; Veciana, Jaume; Casado, Juan
Abstract: A detailed analysis is undertaken of positively charged species generated on a series of thienylenevinylene ( n TV) wires terminally substituted with two perchlorotriphenylmethyl ( . PTM) radical acceptor groups, . PTM‐ n TV‐PTM . ( n =2–7). Motivated by the counterintuitive key role played by holes in the n TV bridges on the operating mechanism of electron transfer in their radical anion mixed‐valence derivatives, a wide combination of experimental and theoretical techniques is used, with the aim of gaining further insights into their structural location. Consequently, contributions of the . PTM units for the stabilization of the radical cations and hole localization, particularly in the case of the shortest molecular wire, are probed. In this sense, the formation of quinoidal ring segments, resulting from the coupling of the unpaired electron of the . PTM radical site with those generated along the n TV chains is found. Additionally, open‐shell dications, described by the recovery of the central aromaticity and two terminal quinoidal segments, assisted by the . PTM units, are detected. Abstract : Molecular wires : A combination of theoretical and experimental techniques, including UV/Vis‐NIR electronic absorption, ESR, and resonant Raman spectroscopies, reveals the role of the terminal . PTM units of the diradical . PTM‐ n TV‐PTM . series in the stabilization of positively charged species generated on the n TV bridges.